2008
DOI: 10.6004/jnccn.2008.0028
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Lung Cancer in Elderly Patients: A Review

Abstract: Small cell lung cancer (SCLC) accounts for approximately 13% of all lung cancer cases. Approximately 40% of those cases are diagnosed in patients older than 70 years, and this proportion continues to rise in contrast to the continued decline in incidence of SCLC among the general population. The optimal strategy to manage limited-stage SCLC involves a combined modality approach with platinum-based chemotherapy and external-beam thoracic radiation therapy. For extensive-stage disease, platinum-based combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Older smokers and former smokers (especially young females) are the highest risk group for developing SCLC. However, approximately 40% of cases are diagnosed in patients older than 70 years of age and this proportion continues to rise in contrast to the continued decline in the incidence of SCLC among the general population [15]. Additionally, the proportion of women with SCLC increased from 28% in 1973 to 50% in 2002 [16] and it has been shown that female gender in limited-stage (LS)-SCLC may be a good prognostic factor of both OS and toxicity.…”
Section: Small-cell Lung Cancer In the Elderlymentioning
confidence: 97%
“…Older smokers and former smokers (especially young females) are the highest risk group for developing SCLC. However, approximately 40% of cases are diagnosed in patients older than 70 years of age and this proportion continues to rise in contrast to the continued decline in the incidence of SCLC among the general population [15]. Additionally, the proportion of women with SCLC increased from 28% in 1973 to 50% in 2002 [16] and it has been shown that female gender in limited-stage (LS)-SCLC may be a good prognostic factor of both OS and toxicity.…”
Section: Small-cell Lung Cancer In the Elderlymentioning
confidence: 97%
“…Platinum-based, frontline chemotherapy has been established as the standard treatment for SCLC patients [17][18][19][20][21], with marked responses in approximately 70% of patients with limited-stage SCLC [22][23][24][25] and in 50% of patients with extensive-stage SCLC [12,13,19,26]. Despite this high initial response to chemotherapy, the majority of SCLC patients experienced relapse and develop drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Majority of these patients have extensive stage of the disease, which is incurable with currently available treatment options. The efficacy of platinum-based chemotherapy for frontline therapy has been established in randomized clinical trials 37 with objective responses in approximately 70% of patients with limited stage SCLC and in 50% of patients with extensive stage disease. 5,8–10 Despite this high initial response, majority of SCLC patients require salvage therapy for disease progression within several months following frontline therapy.…”
Section: Introductionmentioning
confidence: 99%